Long-term and gender-related variation in the feeding ecology of common bottlenose dolphins inhabiting a subtropical estuary and the adjacent marine coast in the western South Atlantic. Issue 1 (2nd January 2017) - Secchi, Eduardo Resende; Botta, Silvina; Wiegand, Marcelo M.; Lopez, Luara Azevedo; Fruet, Pedro Friedrich; Genoves, Rodrigo Cezar; Di Tullio, Juliana Couto
ABSTRACT: We combined stomach content analysis and stable isotopes to investigate long-term changes in the feeding ecology of common bottlenose dolphins ( Tursiops truncatus ) from the Patos Lagoon estuary and adjacent marine coast, southern Brazil, during the past 35 years. Stomach contents of bottlenose dolphins collected between 2002 and 2012 (Period II) were compared to those previously described for this population (1977–1980, Period I), and δ 13 C and δ 15 N values in tooth dentine from specimens collected between 1977 and 2012 were used to assess temporal changes in contribution of the main prey to the diet of dolphins over time. Additionally, these data were used to verify the magnitude of trophic overlap between males and females from Period II. Bottlenose dolphins consumed a wide variety of prey. Demersal and demersal–pelagic teleost fish predominated. These results show that bottlenose dolphins from the Patos Lagoon estuary are opportunistic feeders and confirm the plasticity of the species, which preys upon the most available prey. Differences in diet were found between seasons and periods. Stable isotopes and stomach contents detected a significant long-term change in the proportions of their main prey. The contribution of Micropogonias furnieri and Menticirrhus sp. decreased after 1990 while a significant increase in the importance of Trichiurus lepturus was observed. Males consumed a significantly higher proportion of T. lepturus while Mugil liza was the main prey for females. These changes might be due to fishing-related changes in fish abundance.